Socialization and Training on Making Vegetable Pesticides from Papaya Leaves (Carica papaya. L) and Garlic (Allium sativum) with the Community of Taba Air Pauh Village - Charles Banon; Evi Maryanti; Lisa Anggraini; Miranda Dwi Indriyani; Resika Vanessgia; Saskia Shaumi Wulandari; Noor Haida Mohd Kaus (CV Media Inti Teknologi, 2024)
The use of pesticides in large doses and carried out continuously in each planting season will cause several losses, including pesticide residues that will accumulate in agricultural products and waters, pollution of the agricultural environment, decreased productivity, poisoning of animals, poisoning of humans which has an impact bad for their health. To overcome or reduce the negative impact of these pesticides, an alternative control method that can be used is to use natural pesticides. Natural pesticides are an alternative that can be used to overcome the shortcomings of chemical pesticides. The aim of carrying out this community service activity is to provide knowledge and skills to the people of Taba Air Pauh Village, Tebat Karai District, Kepahiang Regency regarding the use of natural ingredients such as garlic and papaya leaves as natural pesticide ingredients. The method applied in community service activities was socialization and training on pesticides from papaya leaves and garlic. Based on the results of community service activities regarding training in making vegetable pesticides from papaya leaves and garlic, the people of Taba Air Pauh Village, Tebat Karai District, Kepahiang Regency have learned about the dangers of long-term use of chemical pesticides and obtained information regarding other alternative materials for using chemical pesticides by utilizing natural materials around Taba Air Pauh Village.